Legal Responsibility of Business Actors in Guaranteeing Halal Products - Irwansyah, Muh. Gani; Saleh, Moh. (International Journal of Educational Research & Social Sciences, 2024)
This paper examines the legal obligations of businesses in Indonesia concerning halal product assurance, as mandated by Law Number 33 of 2014. It explores the significance of halal certification in protecting consumers, fostering economic growth, and upholding market integrity. The discussion covers legal requirements for businesses, potential sanctions for non-compliance, and the role of certification in building consumer trust and ensuring adherence to halal standards. The paper emphasizes the importance of halal certification for businesses within the halal industry and highlights the legal framework that safeguards consumer rights to genuine halal products. Additionally, it explores the role of government initiatives in developing the domestic halal food industry and maintaining strict halal standards. Overall, the paper underscores the multifaceted benefits of halal certification for businesses, consumers, and the Indonesian economy as a whole.Halal Certification